Barcelona - Suozzo, Mark 1953- (The Criterion collection, 2016)
"Whit Stillman followed his delightful indie breakthrough Metropolitan with another clever and garrulous comedy of manners, this one with a darker edge. A pair of preppy yet constitutionally mismatched American cousins—a salesman and a navy officer—argue about romance and politics while working in the beautiful Spanish city of the film’s title. Set during the eighties, Barcelona explores topics both heady (American exceptionalism, Cold War foreign policy) and hilarious (the ins and outs of international dating, the proper shaving method) while remaining a constantly witty delight, featuring a sharp young cast that includes Taylor Nichols, Chris Eigeman, and Mira Sorvino." [criterion.com]
director-approved DVD special edition features: new, restored 2K digital transfer, supervised by director Whit Stillman and cinematographer John Thomas ; audio commentary from 2002 featuring Stillman and actors Chris Eigeman and Taylor Nichols ; new video essay by film critic Farran Smith Nehme about the trilogy made up of Metropolitan, Barcelona, and The last days of disco ; the Making of "Barcelona," a short documentary from 1994 featuring behind-the-scenes footage and on-set interviews with Stillman and cast members ; deleted scenes and alternate ending, with commentary by Stillman, Eigeman, and Nichols ; segment from a 1994 episode of the Today show featuring Stillman ; Episode of The Dick Cavett Show from 1991 with Stillman ; trailer ; plus: an essay by film scholar Haden Guest
Original: USA 1994
Bildformat 1.85:1
Keywords: Film; DVD-Video